ANALISIS PENGARUH NILAI TUKAR RUPIAH, TOTAL PENJUALAN, DAN LABA BERSIH TERHADAP KINERJA HARGA SAHAM BANK PANIN SYARIAH - Riyan Pradesyah (Universitas Islam Negeri Sumatera Utara, 2016)
The purpose of this research to determine the influence of Exchange Rate,Total Sales, and Net Income againts the Stock Price Performance atPanin Bank Syariah. The samples used in this research are data of NTR, TPJ, Net Income on Stock Price Performance atBank PaninSyariah from January 2010 to December 2015. This research used quantitative research approach that is VAR (Vector Auto Regressive)analysissupported by a stationarity test, optimal lag test,stability test of the VAR model, granger causality test, impulse response functiontest and variance decomposition test, assisted by Eviews software version 6.The results of research conducted by alpha 5%, the authors have concluded that the results of VAR analysis, whichvarince decompositiontest showed that the Exchange Rate, Total Sales, and Net Income variables influence on Stock Price Performance at Bank Panin Syariah. In the short-term or the beginning of the observation period to the end of the observation, the net profit has more dominant influence amounted to 13,87%. While the exchange ratevariable has an influence on the stock price performanceamounted to 0.23%, and total sales variable have an influence amounted to 0.43%. The result of granger causality test showed that all variables have a causal relationship with one another, it means each of variable has 2-way relationship with other variables. While the results impulse response function test showed that the stock pricesperformanceresponded positively and balanced against the exchange rate, responded negatively to the net income variable and approaching equilibrium,and total sales variable responded positively and balanced.So, when tested simultaneously, the most influencevariables is net incomevariable.